HUBUNGAN LITERASI NUMERASI DENGAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VI MI NURUL ITTIHAD KOTA JAMBI - Putri, Nike Naldi; Idris, Ilyas; Saputra, Donal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the relationship between Numeracy Literacy Competence and Critical Thinking Skills among sixth-grade students at MI Nurul Ittihad, Jambi City. This research employed a quantitative correlational approach, involving 37 students as the research sample. Data were collected through two test instruments, namely a Numeracy Literacy test and a Critical Thinking Skills test, each consisting of 20 multiple-choice items, which were confirmed valid and reliable (Cronbach's Alpha of 0.891 and 0.904, respectively). Data were analyzed using Pearson Product Moment correlation and simple linear regression after the normality and linearity assumptions were met. The results show a positive and significant relationship between the two variables, with a correlation coefficient of r = 0.651 (strong category) and Sig. = 0.000 < 0.05. The regression equation obtained was Ŷ = 39.325 + 0.445X, with a coefficient of determination (R²) of 0.424, indicating that Numeracy Literacy Competence contributed 42.4% to students' Critical Thinking Skills. These findings imply the importance of strengthening contextual problem-solving-based numeracy literacy instruction as a strategy to develop students' critical thinking skills at the elementary/madrasah level.